Export Margins, Price and Quantity of Belarus's Export Growth - Shavkat Otamurodov; Shujin Zhu; Ihtisham ul Haq; Tenglong Zhong (Review of Economic Perspectives, 2017)
This paper examines the sources of Belarus's export growth and decomposes export growth into extensive and intensive margins. This study also aims to determine export margins for intermediate and final goods and to determine the price and quantity components of the intensive export margin. In order to achieve the desired objectives, we use two methods for decomposing export growth, the count method and the export shares method. We analyse Belarus's export growth using export data at the HS-6 digit level for the 2004-2014 period. Our results show that Belarus's exports grew mainly due to growth in the price margin during the studied period 2004-2014. However, the extensive margin was important in export growth to some extent. Comparing the growth rate across final and intermediate goods reveals that although the share of final products in Belarus's exports is not very big (18.9% in 2014), the average annual growth in exports of final products is higher than that of intermediate goods. Our investigation also shows that Belarus produces a wide range of commodities, but the share of the most of these commodities is not large; its exports depend on a restricted range of commodities. Moreover, most of the commodities are exported to Russia and Ukraine. Our results give us reason to assume that finding new markets for their new products is one of the main challenges for developing countries wishing to increase their exports by an extensive margin. This has important implications for how policy makers promote the trade and diversification of exports.
Keywords: 330; Export growth; Extensive margin; Intensive margin; Belarus